2007
DOI: 10.1002/art.23132
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging assessment of cognitive function in childhood‐onset systemic lupus erythematosus: A pilot study

Abstract: Objective. To investigate changes in brain activation patterns detected by functional magnetic resonance imaging (FMRI), and the relationship between FMRI activation patterns and results of formal neuropsychological testing, in patients with childhood-onset systemic lupus erythematosus (SLE).Methods. Ten patients with childhood-onset SLE underwent formal neuropsychological testing and FMRI using 3 paradigms: a continuous performance task (CPT) to evaluate attention, an N-Back task to assess working memory, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 80 publications
5
53
0
8
Order By: Relevance
“…language processing tasks (24). Similarly, ST patients in this study demonstrated significantly increased neural activation in cortical areas associated with working memory (cingulate gyrus, prefrontal cortex, somatomotor cortex and BA40) compared with the LT group.…”
Section: Figuresupporting
confidence: 63%
See 1 more Smart Citation
“…language processing tasks (24). Similarly, ST patients in this study demonstrated significantly increased neural activation in cortical areas associated with working memory (cingulate gyrus, prefrontal cortex, somatomotor cortex and BA40) compared with the LT group.…”
Section: Figuresupporting
confidence: 63%
“…Therefore, fMRI provides an objective measure of functional neural networks solicited by specific probes. Three previous fMRI studies in SLE patients compared with healthy controls have all demonstrated abnormally increased regional brain activation patterns in areas targeted by specific tasks (24)(25)(26). We asked whether these abnormalities also correlate with disease duration.…”
Section: Differences In Regional Brain Activation Patterns Assessed Bmentioning
confidence: 95%
“…However, the structural MRI has been found to be of limited value in patients with diffuse neuropsychiatric disturbances such as headache, cognitive dysfunction, affective disorders, and confusional states [Rozell et al, 1998;Sabet et al, 1998]. Multiple functional neuroimaging modalities have therefore been used in SLE, including 1 H-magnetic resonance spectroscopy (MRS) [Castellino et al, 2005], SPECT [Appenzeller et al, 2007a], and fMRI [DiFrancesco et al, 2007;Fitzgibbon et al, 2008;Rocca et al, 2006]. These studies have suggested that functional alterations could precede structural changes in NP-SLE [Castellino et al, 2005], and, moreover, they allowed differentiation between patients with or without active CNS involvement [Appenzeller et al, 2007a].…”
Section: Discussionmentioning
confidence: 99%
“…This method uses deoxyhemoglobin as an endogenous contrast agent to identify areas of altered perfusion. Earlier fMRI studies reported that brain functions including working memory [Fitzgibbon et al, 2008], motor control [Rocca et al, 2006] and cognitive function [DiFrancesco et al, 2007] are altered in SLE patients with central nervous system (CNS) involvement. However, because these studies were generally performed with NP-SLE patients, it is unclear whether the observed changes represent alterations that progressively give rise to neuropsychiatric complications or are a consequence of disease progression following the emergence of neuropsychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In a key study by DiFrancesco et al, 54 fMRI was combined with a (non-CARRA or PED-ANAM) battery of standardized neuropsychological tests, to demonstrate significant agedependent activation differences in 10 patients with childhood-onset SLE compared to healthy age-matched controls, in the attention [using continuous performance task (CPT)], working memory (using N-back task) and language paradigms (using verbal generation task). A deficit in word fluency in childhoodonset SLE seemed to correlate with reduced activation in the Wernicke area and altered activation in the Broca areas involved in wordfinding and language processing.…”
Section: Association Of Regional Brain Activity and Domains Of Neurocmentioning
confidence: 99%